Carotenoids of Capsicum Fruits: Pigment Profile and Health-Promoting Functional Attributes - Norazian Mohd Hassan; Nurul Asyiqin Yusof; Amirah Fareeza Yahaya; Nurul Nasyitah Mohd Rozali; Rashidi Othman (MDPI AG, 2019)
Pepper of the Capsicum species is a common ingredient in various food preparations by different cultures worldwide. The Capsicum is recognised by its five main domesticated species, namely Capsicum annuum, C. baccatum, C. chinense, C. frutescens and C. pubescens. The genetic diversity in Capsicum offers fruits in wide ranges of morphology and carotenoid profile. Carotenoids enhance the value of pepper from a nutritional standpoint, despite being commonly prized for the pharmacologically active pungent capsaicinoids. Carotenoids of pepper comprise mainly of the unique, powerful and highly stable capsanthin and capsoroubin, together with β-carotene, β-cryptoxanthin, lutein, zeaxanthin, antheraxanthin and violaxanthin. These carotenoids are present at diverse profile and varying levels, biosynthetically connected to the fruit maturity stages. This review describes the health-promoting functional attributes of the carotenoids that are mainly associated with their excellent role as lipophilic antioxidants. Capsicum as a great source of carotenoids is discussed in the aspects of main domesticated species, biosynthesis, pigment profile, antioxidant activity and safety. Findings from a number of in vitro, in vivo and clinical studies provided appreciable evidence on the protective effects of pepper’s carotenoids against degenerative diseases. Hence, pepper with its functional carotenoids might be recommended in health-promoting and disease preventing strategies.